A comparison of the relationship between ground-measured particulate matter and aerosol optical depth derived from both Sentinel-3a and AERONET - CAITLIN JONES (2024)
In this thesis, the linear correlation of remotely sensed aerosol optical depth (AOD) and ground-measured fine particulate matter (PM2.5) is investigated. With instruments that are commonly usedto derive the concentrations of PM2.5 using remote sensing and AOD correlation, such as MODIS,going past its expected operation period, new instruments must be investigated to determine if theywill be suitable for AOD and PM2.5 studies in the future.In this study, Sentinel-3a AOD data, derived from the Swansea University aerosol retrieval algorithm,was used to investigate the linear relationship between remotely sensed AOD and ground-measuredPM2.5 at the city scale. City pixels of AOD were correlated against aggregated PM2.5 stations, andcompared against the correlations of AERONET, a well-established ground measured AOD dataset, to see how they performed. This was conducted at a city-wide scale.This study showed a similar performance in the R2 values between Sentinel-3a and AERONET whencorrelating monthly values, but with R2 values remaining low. The main conclusions were thatSentinel-3a datasets have the potential to estimate PM2.5, but further research must be conducted in order to determine the best approach, as the city-scale may not be appropriate due to the coarseresolution.